Comparison of Bacterial Load measured by X-pert / MTB RIF Assay with Smear & Myco-Bacterial Culture, as a marker for monitoring disease outcome in Cavitary Pulmonary Tuberculosis - Aisha Shafique, Sara Daud, Asma Sabir, Kanwal Fatima Khalil, Amber Mazhar, Anum Ilyas (Journal of Rawalpindi Medical College, 2022)
Introduction: Tuberculosis (TB) is one of the major public health problems in Pakistan. Treatment depends on the diagnosis and bacterial load. The smear and culture of the sputum sample are considered as the gold standard. However, another recently invented diagnostic criteria i.e. X-PERT / MTB RIF Assay can also give high accuracy and can be used as a substitute for sputum culture. Objective: To determine the validity of Xpert MTB/RIF and sputum smear in monitoring the outcome of cavitary pulmonary tuberculosis by taking culture as the gold standard Study design: Descriptive Cross-sectional Study. Setting: Department of Pulmonology, Fauji Foundation Hospital Rawalpindi. Duration: 15th Feb to 15th Dec 2018. Materials and Methods: 250 Patients who meet the criteria were integrated into the study. A sputum sample was taken two times and two samples were sent to the laboratory of the hospital for Xpert MTB/RIF, sputum smear, and culture. Findings were recorded. Then patients were given standard treatment for tuberculosis. Data was entered in SPSS 23. Age, laboratory variables like HB, Platelets count, etc. were presented as mean and standard deviation. Gender, outcome of diagnosis were presented as mean and standard deviation. Sensitivity, specificity measure on –rays, findings, smear test, and Xpert MTB/RIF. Results: Total 187 patients including 12 (6.4%) male and 175 (93.6%) female. The mean age was 44.14+17.13 years. Positive findings on X-pert and smear were found in 35(53%) patients and MTB/ RIF were found in 41(62.1%). Sensitivity, specificity of X-pert MTB/RIF were found to be 77.6% and 13.6% at baseline while 40% and 40% respectively at end of treatment. Conclusion: Thus, X-pert MTB/RIF is an important tool than sputum smear and AFB culture in monitoring the outcome of cavitary pulmonary tuberculosis.